Vascular complications in living-related and deceased donation pediatric liver transplantation: Single center's experience from Turkey - Yilmaz, Aygen; Arikan, Cigdem; Tumgor, Gokhan; Kilic, Murat; Aydogdu, Sema (Pediatric transplantation, 2007)
:  The aim of the study was to assess early and long‐term incidence of venous complications, in both deceased donation (DD) and living‐related (LR) liver transplantation (LT) in a pediatric population. Seventy‐five liver transplants performed in 69 (39 boys, 30 girls) children at Ege University Hospital between 1997 and 2004 were prospectively monitored and reviewed. Age, sex, primary diagnosis, graft type, vascular complications and their management were evaluated. All patients received Doppler ultrasonographic examination both during operation and daily for the first three postoperative days and when necessary thereafter. The complications were classified as early and late presented. Thirty‐three grafts (47.8%) were from DD and 36 (52.2%) were from LR donors. Recipients of DD were older than LR donors (mean age 10.5 ± 5.1 and 5.0 ± 0.7, respectively) (p < 0.05). Vascular complication occurrence was not statistically different between DDLT and LRLT recipients (p = 0.2), and between infants and children (p = 0.9). Overall, stenosis was more common than thrombosis. We observed hepatic artery (HA) thrombosis, in five of 75 (6.7%) transplants within 30 days post‐transplant. Portal vein (PV) thrombosis and hepatic vein (HV) thrombosis were detected in six and one patients (8.7% and 1.3%), respectively. Six PV stenosis were identified (8.7%), while HA and HV‐VC (vena cava) stenosis occurred in one and six patients (1.4% and 8.7%), respectively. All PV stenosis (6/33, 18.2%) and one PV aneurysm occurred in DDLT recipients while HV‐VC stenosis were detected almost equally in LRLT and DDLT recipients (4/36 vs. 2/33). Except one, all PV stenosis were detected as a late complication and no intervention were needed. Stenosis of HV‐VC was more common in girls (5/30 vs. 1/39) (p < 0.05) and the incidence was not different in DDLT and LRLT recipients (p = 0.8). In conclusion, overall incidences of thrombosis and stenosis formation after orthotopic liver transplantation (OLT) were 17.4% and 18.8%, respectively in our center. We suggest that in the cases with HA thrombosis manifested intra‐operatively or within the early postoperative period, graft salvage was successful. Thrombosis of HA causes significant mortality. Thrombosis of PV was among the causes of mortality and morbidity. Stenosis of HV‐VC could be managed by angioplasty and endovascular stenting with no significant effect to mortality.